The Economics of Rural Electrification Projects: Theory and Case Study of Pakistan (The Pakistan Development Review, 1982)
Developing countries will invest significant resources in rural electrification projects in the 19805. Up to now, there has been little discussion in the economics literature concerning the appropriate method of evaluating such projects. This paper outlines such a methodology and, then, it is applied in a case-study of a proposed rural electrification project in Pakistan. Finally, important areas for future research are identified.